Deepening system leadership: Teachers leading from below. (January 2016) - Boylan, Mark
The increasing importance of educational collaborations and networks that blur organizational boundaries requires conceptual developments in leadership theory. One approach to both theorizing and promoting such phenomena is through the idea of system leadership. Three different meanings of the term are identified: interschool leadership; a systemic leadership orientation and identity; and leadership of the school system as a whole. Previous descriptions of system leadership, and policy initiatives related to it, have focused on headteachers and senior leaders. However, teacher leaders may also exercise system leadership in relation to all three meanings. Professional development networks and school collaborations provide a range of distinct contexts for interschool leadership by teacher leaders and these are identified. This extends existing theories of teacher and distributed leadership. Further, it is proposed that teacher leaders can, like headteachers, have a systemic leadership practice orientation that is informed by moral purposes. The model of teacher activist professional identity provides a starting point for analysing teacher system leadership identity. Teacher leaders can and do influence system-wide change and, to conceptualize this, the concept of system leadership from below is introduced. In making this argument a number of issues and methodological tools are identified that are important in researching both headteacher and teacher system leadership in relation to the three meanings of system leadership.